Guiding early educators with andragogy: a mixed-methods case study of new teacher induction, support, and development - Moskowitz, Ellen S. (Kansas State University, 2024)
This study set out to evaluate the effectiveness of a multi-year new-teacher induction program, which encompassed a first-year mentoring component and four years of continuous professional development to support new teachers during their pre-tenure phase. Using a mixed methods case study approach, the research sought to determine the most beneficial professional supports for new teachers, gauge the influence of sustained professional development on them, examine the correlation between the program and (1) new teacher retention, (2) self-efficacy, and (3) overall job satisfaction, and assess the broader impact of a new teacher induction program on teacher quality. Data collection involved both qualitative and quantitative methods, including surveys, interviews, and the analysis of teacher retention and evaluation data. The study employed Logit model regression analyses for teacher retention data to explore retention odds ratios and Fixed Effect Regression models to scrutinize teacher evaluation data, investigating the impact of various factors on teacher evaluation scores. Key findings demonstrated that the Grow to Great induction program notably enhanced teachers' self-efficacy, pedagogical skills, professional learning communities, and access to support systems. Nevertheless, the program's sustainability faced challenges due to elevated attrition rates within the school or district, affecting teachers' engagement in the program. These results underscore the significant influence of school climate on teachers' capacity to learn and develop professionally. The implications of this research stress the need for continuous professional support for new teachers throughout their pre-tenure years and the critical importance of identifying effective support mechanisms for their development. Future research should prioritize conducting longitudinal studies to evaluate the long-term impact of new teacher induction programs on teaching practices and student assessment scores, thus shedding light on their enduring contributions to educational quality. Research should also delve into strategies, interventions, and support systems designed to bridge the learning gap between veteran and pre-tenured educators adopting research-based best practices. A longitudinal approach will offer insights into challenges, successes, and the role of ongoing professional development in sustaining improvements. Additionally, there is a need for research focused on developing a teacher evaluation system that guarantees reliability and transparency while fostering intrinsic motivation among educators, encouraging continuous improvement in instructional practices. Such a system should place emphasis on constructive feedback and personalized development pathways to ultimately enhance overall teaching quality and empower educators.
Keywords: New teacher induction; Teacher evaluation; Teacher retention; School climateAndragogy